Evaluating Ammonia (NH3) Predictions in the NOAA NAQFC for Eastern North Carolina Using Ground Level and Satellite Measurements. Issue 14 (29th July 2019) - Battye, William H.; Bray, Casey D.; Aneja, Viney P.; Tong, Daniel; Lee, Pius; Tang, Youhua
Abstract: Ammonia (NH3 ) in the atmosphere contributes to the formation of airborne fine particulate matter (PM2.5 ), which is associated with adverse human health effects. The emission, transport, reactions, and deposition of NH3 in the atmosphere are modeled using the Community Multiscale Air Quality (CMAQ) model, within the U.S. National Air Quality Forecast Capability (NAQFC). The purpose of this current work is to evaluate the capability of the NAQFC CMAQ model and to identify potential improvements to NH3 emissions estimates and prediction methods. This study focuses on CMAQ predictions of atmospheric NH3 in North Carolina, including a region with intensive animal production and enhanced NH3 emissions. The CMAQ model is run for July 2011 using a version of the 2011 National Emissions Inventory in which agricultural NH3 emissions were adjusted to reflect the lower end of the range of estimates from the current process‐based emissions model. The NAQFC CMAQ model overpredicted atmospheric NH3 at a continuous monitor in Clinton, NC, within the region of intensive animal production. The average concentration measured by the monitor was 6.6 ppbv, while the average predicted by the model was 10.5 ppbv, a 60% overprediction. Outside of the region of intensive animal production, both measured and modeled NH3 concentrations were low, 1.3 ppbv or less. The model underpredicted wet deposition of NH4 + and dry deposition of NH3 . It is believed that the overestimation of NH3 at Clinton is attributable at least in part to the underestimation of wet and dry deposition in North Carolina. Key Points: The National Air Quality Forecast System model overpredicted ammonia at a continuous monitor in a region of intensive animal production Model predictions for ammonia were improved by using State permit information for locations of animal feeding operations The model underpredicted wet deposition of ammonium ion and dry deposition of ammonia in eastern North Carolina